Kohesi Dan Koherensi Dalam Wacana Komik Bahasa Indonesia - I Gusti Ngurah Mayun Susandhika (Jurnal Ilmiah Cakrawarti, 2018)
The marker of substitutional cohension can be found in three types: nominal,verbal, and clausal substitutional cohesion. The nominal substitutional cohension hastwo subtypes: personal and non-personal of nominal substitutional cohension. Meanwhile,the marker of ellipsis cohension differentiated into three types: nominal, verbal,and chaulsal ellipsis cohesion. The conjunctive cohension is differentiated into five typemarke: additive, adversative, temporal, continuative, and causal. The lexical cohensionis differentiated into four types: reiterative, synonimy, hyponimy, and colocative lexicalcohension.While in the coherence of comic discourse shows the existence of two systems of theforming coherence, namely coherence based on the cohesion systems, and the coherencebased on the situational aspects. The coherence based on the cohension system canbe differentiated into four types: equal, pposite, successive, situational aspects has twotypes, namely continuity step of situational coherence, and the explanation situasionalcoherence.